GENETICS OF LARGE PIGMENT EPITHELIAL DETACHMENTS IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 4 (April 2020) - Mouallem-Beziere, Alexandra; Blanco-Garavito, Rocio; Richard, Florence; Miere, Alexandra; Jung, Camille; Rozet, Jean-Michel; Souied, Eric H.
Abstract : Purpose: We hypothesized that severe forms of neovascular age-related macular degeneration (AMD) such as large pigment epithelial detachments poorly responding to anti–vascular endothelial growth factor therapy might present a distinct genotype compared with overall series of neovascular AMD. Methods: This is a multicenter genetic association study. Sixty-eight patients presenting pigment epithelial detachments resistant to ranibizumab (issued from ARI2 study, register number NCT02157077 on clinicaltrials.gov ) were compared with two series of patients derived from previously published clinical studies, presenting neovascular AMD (NAT2 study n = 300 and PHRC study n = 1, 127), and with healthy controls (n = 441). The phenotype of neovascular AMD groups was based on visual acuity measurement, fundus examination, spectral-domain optical coherence tomography, and angiographic data. All samples were genotyped for three single-nucleotide polymorphisms: CFH ( rs1061170 ), ARMS2 ( rs10490924 ), and C3 ( rs2230199 ). Significant difference in allele frequency between participants with neovascular AMD and control was the main outcome measurement. Results: The GG genotype of the C3 rs2230199 was significantly more frequent in the ARI2 group (55.9%) than the PHRC group (6.0%, P < 0.0001; odds ratio = 24.0 [95% confidence interval 10.4–55.0]) and the NAT2 group (5.1%, P < 0.0001; odds ratio = 16.1 [95% confidence interval 5.0–51.9]). The repartition of patients carrying a T allele of the ARMS2 ( rs10490924 ) or patients carrying a C allele of the CFH ( rs1061170 ) was similar in the ARI2 group when compared with the NAT2 and PHRC groups. Conclusion: In our series, the genotype GG of C3 rs2230199 was more significantly associated with the phenotype of large vascularized pigment epithelial detachment poorly responding to anti–vascular endothelial growth factor therapy than in global AMD series. Abstract : The present study reveals that the genotype GG of C3 rs2230199 may be significantly associated with large vascularized pigment epithelial detachments that poorly respond to treatment, when compared with a global age-related macular degeneration series.